Vaccinating people who have had covid-19: why doesn't natural immunity count in the US?. (13th September 2021) - Block, Jennifer
Abstract : The US CDC estimates that SARS-CoV-2 has infected more than 100 million Americans, and evidence is mounting that natural immunity is at least as protective as vaccination. Yet public health leadership says everyone needs the vaccine. Jennifer Block investigates